Pengaruh Citra Merek dan Kepercayaan Merek terhadap Loyalitas Merek Konsumen Muda Kota Padang di Kafe Lokal Modern House of Musi - Fadillah, Rifky; Sari , Dessy Kurnia; Ma’ruf, Ma’ruf (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the influence of brand image and brand trust on brand loyalty using Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis results demonstrate that both brand image (β = 0.361, p < 0.001) and brand trust (β = 0.414, p < 0.001) have a positive and significant effect on brand loyalty, with brand trust exhibiting a more dominant influence.The model meets acceptable reliability criteria (Composite Reliability ≥ 0.824) and convergent validity (AVE ≥ 0.5), while an R² value of 0.514 indicates that 51.4% of brand loyalty variance can be explained by these two predictors. Although the SRMR value (0.084) slightly exceeds the ideal threshold (0.08), the model remains statistically valid with no multicollinearity issues (VIF < 2.006).The findings conclude that marketing strategies should prioritize strengthening brand trust as a key driver of loyalty, without neglecting the role of brand image. This study provides an empirical foundation for businesses in developing customer loyalty strategies and recommends exploring additional variables to explain the remaining 48.6% of unexplained variance.